1961
DOI: 10.1007/bf01421749
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for the importance of residual leaf protein complexes in litter decomposition and the supply of nitrogen for plant growth

Abstract: been air dried. Thus Calluna vulgaris leaf extract--gelatin complex was less readily solubihzed than the Chamaenerion angusti/olium leaf extract--gelatin complex.If this resistance to solubilization is the basis of a resistance --37 --

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

1963
1963
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 20 publications
2
31
0
3
Order By: Relevance
“…Initial absolute increases were observed in LM litter and are similar to those observed in other studies for lignin (Kaushik & Hynes 1968, Triska et al 1975, Suberkropp et al 1976) and nitrogen (Mikola 1955, King & Heath 1967, Odum et al 1979. These increases may have resulted from the formation of insoluble complexes from the binding of proteins and soluble phenolics present in the plants at the time of senescence (Handley 1961). No such increase occurred during the first 2 wk of decay in CB this study initially contained 11 to 12 % lignin means f SE (Fig.…”
Section: Bound Phenolicssupporting
confidence: 88%
See 1 more Smart Citation
“…Initial absolute increases were observed in LM litter and are similar to those observed in other studies for lignin (Kaushik & Hynes 1968, Triska et al 1975, Suberkropp et al 1976) and nitrogen (Mikola 1955, King & Heath 1967, Odum et al 1979. These increases may have resulted from the formation of insoluble complexes from the binding of proteins and soluble phenolics present in the plants at the time of senescence (Handley 1961). No such increase occurred during the first 2 wk of decay in CB this study initially contained 11 to 12 % lignin means f SE (Fig.…”
Section: Bound Phenolicssupporting
confidence: 88%
“…Previous studies have generally employed the method of Van Soest (1963) for lignin determinations in decaylng litter (Triska et al 1975, Suberkropp et al 1976, Godshalk & Wetzel 1978a, 1978b, although this technique potentially overestimates lignin concentrations since complexes formed by the binding of nitrogenous compounds by phenolics (Handley 1961, Van Sumere et al 1975, Swift et al 1979) are reported as lignin (Suberkropp et al 1976). Lignin determinations by the UV absorption method are not subject to such interference (Morrison 1972a(Morrison , 1972b, but do assume that the molar absorptivity ( E~~~) of the residual lignin is unaltered by decay (Crawford 1981).…”
Section: Bound Phenolicsmentioning
confidence: 99%
“…Handley ( 1961) has found that tannins reduce the ability of microbial organisms to break down leaf protein, owing to the formation of leaf proteintannin complexes. Tannins are known to inhibit th~ growth of fungi (e.g., Wise and Jahn 1952, Pndham 1960, Swain and Bate-Smith 1962, Williams 1963 and the transmission of viruses (Bawden andKleczkowski 1945, Cadman 1960), probably by tanning the fungal pectolytic enzymes (Byrde, Fielding, andWilliams 1960, Williams 1963) and the virus nucleoprotein (White 1956, Cadman 1960).…”
Section: Defensive Function Of Tannins In Plantsmentioning
confidence: 99%
“…Tannin-protein complexes are difficult to mineralise, and subsequently, they determine the proportions of nitrogen released in dissolved organic and inorganic forms (NH 4 ? , NO 3 -) (Handley 1961;Northup et al 1995) Ericaceous plants can use organic nitrogen more efficiently due to symbiosis with ericoid mycorrhizal fungi (Bending and Read 1997). Via the exudative enzymes, these fungi are able to solubilise tanninprotein complexes (Bending and Read 1997).…”
Section: Introductionmentioning
confidence: 99%